2022
DOI: 10.3390/ijms231710015
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the NAC Gene Family in Alfalfa Revealed Its Potential Roles in Response to Multiple Abiotic Stresses

Abstract: NAC (NAM, ATAF1/2, and CUC2) transcription factors compose one of the largest families of plant-specific transcription factors; they are widely involved in plant growth and development and have especially important roles in improving stress resistance in plants. However, NAC gene family members in alfalfa (Medicago sativa L.) have not been systematically identified and analyzed genome-wide due to the complexity of the alfalfa reference genome. In this study, a total of 421 M. sativa NAC genes (MsNACs) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In this study, most of the AsNAC proteins had all of the five subdomains, whereas some domain regions were incomplete in the minority proteins. Similar results were also observed in some previous studies ( He et al, 2022 ; Yang et al, 2022 ), indicating that some NAC proteins possessed preternatural structures and unique functions. It is reported that subdomains A, C, and D are more conserved than B and E ( Ooka et al, 2003 ; Wang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, most of the AsNAC proteins had all of the five subdomains, whereas some domain regions were incomplete in the minority proteins. Similar results were also observed in some previous studies ( He et al, 2022 ; Yang et al, 2022 ), indicating that some NAC proteins possessed preternatural structures and unique functions. It is reported that subdomains A, C, and D are more conserved than B and E ( Ooka et al, 2003 ; Wang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Here, 86 NAC proteins were identified in A. mongolicus. Compared with the genomes of other species, the count of NAC genes in other species such as M. sativa [58], Glycine max [59], Dendrobium officinale [60], and Zanthoxylum bungeanum [29] stands at 421, 269, 111, and 109, respectively. A. mongolicus exhibits a relatively modest count of NAC family members compared to these plants, potentially indicative of evolutionary adaptations in distinct species amid varying habitat conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Gene duplication events act as a significant factor in expansions and realignments of genomes ( Rehman et al., 2022 ). Plenty of transcription factor families have been reported to experience gene duplication events, like bHLH, NAC, and R2R3-MYB families ( He et al., 2022 ; Liang et al., 2023 ; Yang et al., 2023 ). We found 3, 5, and 6 pairs of segmental duplication events in GuARRs , GiARRs , and GgARRs , respectively ( Figure 5 ), while there were no tandem duplications identified, indicating that segmental duplications were the main driving force for the expansion of licorice ARR genes.…”
Section: Discussionmentioning
confidence: 99%